E3XR: An Analytical Framework for Ethical, Educational and Eudaimonic XR Design - Lee, Joey J.; Hu-Au, Elliot (Frontiers in Virtual Reality, 2021)
A rapidly growing number of educators and students now embrace XR as a powerful technology with affordances that can support many benefits, including highly immersive learning experiences, empathy, and perspectives on social issues; XR can be designed in ways that can provide new pathways to success and opportunity. Yet the mirror image is also true -- XR can be designed in ways that lead to increased risk, perpetuation of inequities and other harmful impacts to individuals and society. We need ways to analyze XR in terms of ethical aspects, educational efficacy, and whether it supports or hinders human flourishing (i.e., eudaimonia). In this paper, we discuss XR as a double-edged sword that can be leveraged for positive or negative outcomes, whether intentionally or unintentionally; that is, we highlight various opportunities and benefits at hand, but also risks and possible negative impacts. We introduce E3XR, a framework that serves as an analytical lens to determine the ethics, learning theory and human flourishing aspects of an XR design. For each component of this framework, we review relevant literature and consider the threats and opportunities that can be evaluated. Finally, we conclude with a discussion of the significance of this work and implications for designers and educators.